Employment protection in dual labor markets: Any amplification of macroeconomic shocks? - Benjamin Lochner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2014)
Although labor market duality is a widespread phenomenon in many OECD countries, there is yet no research consent on the effects of duality on labor market dynamics and performance. Against this background, using a New Keynesian model with unemployment, this paper theoretically investigates the importance of labor market duality on labor market volatilities. The new insight is that duality leads to a non-linear reaction of unemployment volatility for both supply and demand shocks. A subsequent empirical panel data analysis confirms the model predictions. Uncovering the non-linearity in unemployment volatility helps reconciling previous divergent research results.
Keywords: E24; E32; E52; J23; J41; J63; 330; Dual Labor Market; Employment Protection; Firing Costs; Unemployment